Risk management with derivatives : interest rate and foreign exchange rate. - Ong, Shui Qi. (2012)
This thesis examines if a company risk management policy to hedge interest rate risk and foreign exchange rate risk affects the volatility of the stock and the default risk of the corporation. This paper would focus predominantly on the usage and effectiveness of financial derivatives in a firm’s risk management practices to reduce interest rate risk and foreign exchange rate risk.